2011
DOI: 10.1038/nrrheum.2011.68
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of systemic juvenile idiopathic arthritis: some answers, more questions

Abstract: Systemic juvenile idiopathic arthritis (sJIA) has long been recognized as unique among childhood arthritides, because of its distinctive clinical and epidemiological features, including an association with macrophage activation syndrome. Here, we summarize research into sJIA pathogenesis. The triggers of disease are unknown, although infections are suspects. Once initiated, sJIA seems to be driven by innate proinflammatory cytokines. Endogenous Toll-like receptor ligands, including S100 proteins, probably syne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
286
0
23

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 291 publications
(319 citation statements)
references
References 104 publications
5
286
0
23
Order By: Relevance
“…Many alleles of HLA-DRβ1, including HLA-DRB1*11 (16), have been reported to affect sJIA risk in studies of single populations (11)(12)(13)(14)(15)(16). However no association has reached the level of genome-wide significance and no single HLA-DRB1 allele has been found to influence sJIA risk across studies or populations (9,17), leading some to conclude that class II HLA molecules are not risk factors for sJIA (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many alleles of HLA-DRβ1, including HLA-DRB1*11 (16), have been reported to affect sJIA risk in studies of single populations (11)(12)(13)(14)(15)(16). However no association has reached the level of genome-wide significance and no single HLA-DRB1 allele has been found to influence sJIA risk across studies or populations (9,17), leading some to conclude that class II HLA molecules are not risk factors for sJIA (18).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, intracellular class II HLA molecules are important regulators of Toll-like receptor signaling in both monocytes and dendritic cells (24). Given that sJIA is a disease marked by systemic inflammation with enhanced production of proinflammatory cytokines (3,17), it is attractive to hypothesize that HLA-DRB1*11 molecules contribute to sJIA pathogenesis through dysregulation of innate immunity and promotion of proinflammatory cytokine production by APCs.…”
Section: Drαmentioning
confidence: 99%
“…Recently, the characterization of autoinflammatory diseases has led to a renewed classification of immune-mediated rheumatic diseases [27]. Recent reports suggest that s-JIA is more likely to belong to the group of autoinflammatory diseases that follow the same continuum as AOSD [12,28,29]. However, whether s-JIA and AOSD are the same disease remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that inflammatory cytokines, including interleukin (IL)-1, IL-6, IL-18, interferon (IFN)-γ, and tissue necrosis factor (TNF)-α play pathogenic roles in the disease processes of both s-JIA and AOSD [12,13]. Furthermore, biological therapies intended to block these cytokines yield dramatic effects in patients with s-JIA and AOSD [14,15].…”
mentioning
confidence: 99%
“…До недавнего времени для лечения системного ЮИА требовалась длительная терапия глюкокортикостерои-дами (на протяжении 3 и более месяцев [4]) в высоких дозах [5,6], что является одним из факторов риска раз-вития остеопороза и вызывает серьезные побочные эффекты, в том числе остеопороз с обширными пере-DOI: 10.15690/pf.v13i6.1669 561 ломами [7,8]. С внедрением в терапию ревматических заболеваний генно-инженерных биологических препа-ратов, которые избирательно воздействуют на иммунную систему и позволяют устранить необходимое звено в патогенезе, появилась возможность уменьшить частоту и длительность применения стероидных гормонов и, тем самым, избежать развития осложнений [6].…”
Section: обоснованиеunclassified